Understanding and Developing Student Assessment Literacy Translating Research into Actionable Approaches - Yang, Min.; Yan, Zi.; Yang, Lan.; Zhan, Ying.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This book provides research-based approaches and classroom strategies for frontline teachers and practitioners, to aid them in formulating actionable approaches to develop student assessment literacy (SAL) in school and higher education sectors. This book helps readers to: Understand the concept of SAL and its significant role in assisting students$1 (Bachievements of desirable learning goals Design and implement supportive classroom strategies for inducting students to the basic knowledge and skills for exercising SAL, and to engage actively and effectively in assessment and learning processes Reflect critically on, and improve their own classroom practices to promote SAL among students This book serves as a valuable reference for a wide range of audiences, including frontline teachers and curriculum leaders in schools and universities, undergraduate and post-graduate students in teacher education and other educational fields, educational service providers, and government officers in educational departments. This is an open access book.s
Chapter 1. Introduction: Conceptualising student assessment literacy (Min Yang) -- Chapter 2. Using self-assessment to develop student assessment literacy (Zi Yan) -- Chapter 3. Peer assessment: A powerful way to cultivate student assessment literacy (Ying Zhan) -- Chapter 4. Student feedback orientations as building blocks of student assessment literacy (Lan Yang) -- Chapter 5. Conclusion: Moving student assessment literacy research and practice forward (Min Yang).
Keywords: Teachers -- Training of; Study Skills; Educational tests and measurements; Teaching and Teacher Education; Study and Learning Skills; Assessment and Testing